2010
DOI: 10.2976/1.3338707
|View full text |Cite
|
Sign up to set email alerts
|

The organization of the secretory machinery in chromaffin cells as a major factor in modeling exocytosis

Abstract: (2010) The organization of the secretory machinery in chromaffin cells as a major factor in modeling exocytosis, HFSP Journal, 4:2, 85-92

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 30 publications
0
18
0
Order By: Relevance
“…But how does this distribution related with the organization of the cortical region in these neuroendocrine cells? Our studies show that the cortical region is structured as an intricate network of F-actin polygonal cages (Giner et al 2005Villanueva et al 2010). This cortical network re-organizes during cell stimulation changing from an intricate structure imprisoning the vesicles in resting conditions to provide open spaces allowing vesicle access to docking sites during secretion (Giner et al 2005).…”
Section: Organization Of the Secretory Machinery In Association With mentioning
confidence: 94%
See 2 more Smart Citations
“…But how does this distribution related with the organization of the cortical region in these neuroendocrine cells? Our studies show that the cortical region is structured as an intricate network of F-actin polygonal cages (Giner et al 2005Villanueva et al 2010). This cortical network re-organizes during cell stimulation changing from an intricate structure imprisoning the vesicles in resting conditions to provide open spaces allowing vesicle access to docking sites during secretion (Giner et al 2005).…”
Section: Organization Of the Secretory Machinery In Association With mentioning
confidence: 94%
“…During these cortical re-organizations vesicles moved on the surface of the dynamic F-actin-myosin II structures (Giner et al 2005). Interestingly, we have recently demonstrated that the SNARE clusters formed by exogenous SNAP-25 also associated with the limits of the polygonal F-actin structures in contact with the chromaffin cell plasma membrane (borders of the cytoskeletal cages, Villanueva et al 2010), therefore these structures seem to organize the secretory machinery in a dynamic environment. The importance of cytoskeletal cage borders is stressed when the site of granule exocytosis is studied in relation with these structures (Villanueva et al 2010).…”
Section: Organization Of the Secretory Machinery In Association With mentioning
confidence: 97%
See 1 more Smart Citation
“…Introducing the cytoskeletal organization as a factor influencing secretion in mathematical models of neurite-emitting chromaffin cells As we have described, the cytoskeletal organization could be another factor influencing the secretory behaviour in the neurites and the cell body Villanueva et al 2010;Gutierrez & Gil 2011;TorregrosaHetland et al 2011). The active role of the cytoskeletal cages was incorporated in our model because these cages act as diffusion barriers for mobile particles in the intracellular medium.…”
Section: Modelling Calcium Channel Influence In the Secretion Of Neurmentioning
confidence: 99%
“…Thus, the study of the secretory organization in neurite-alike structures in chromaffin cells appeared interesting to understand the fine-tuning of exocytosis when the endocrine organization evolves to a pseudoneuronal system. In addition to studying such organization, we use stochastic models of secretion (Gil et al 2000;Torregrosa-Hetland et al 2010Villanueva et al 2010) to study the influence of calcium channel accumulation and cytoskeletal organization in determining the kinetic differences in secretion found between neurite terminals and the cell body. Our study enriches the variety of roles assumed by the cortical cytoskeleton when governing the secretory process (Gutierrez 2012).…”
Section: Introductionmentioning
confidence: 99%